MODEL PENANGANAN PERILAKU MALADAPTIF ANAK BERBASIS PANTI - Mayaut, Flores George; Istanto, Istanto (Istek Widuri Jakarta, 2021)
This study discusses the role of social workers in handling maladaptive behavior in children at PSAA Putra Utama 2 North Jakarta